Synthesis and biochemical characterisation of fluorinated analogues of pepstatin A and grassystatin A. Issue 12 (22nd March 2018) - Lawer, Aggie; Nesvaderani, John; Marcolin, Gabriella M.; Hunter, Luke
Abstract: Pepstatin A and grassystatin A are natural, statine-containing peptides that act as inhibitors of aspartic protease enzymes. In this work, stereoselective fluorination is investigated as a strategy for enhancing the pharmacodynamic and pharmacokinetic properties of these lead compounds. Fluorination is found to modestly affect the protease inhibitory potency, leading to the identification of two highly active new inhibitors of the cancer-associated protease, cathepsin D. However, no dramatic changes are observed in terms of target selectivity, lipophilicity, membrane permeability or metabolic stability. Graphical abstract: